Upaya Peningkatan Hasil Belajar Matematika Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Berbantuan LKS Pada Siswa Kelas VIII SMP Makassar Raya - Abdul Hadi (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
This study aims to determine whether TPS of cooperative learning model can improve students' mathematics learning outcomes. The research was classroom action research (CAR) which was carried out in 2 cycles. Each cycle included four stages, namely: planning, implementation, observation, and reflection. The subjects of this study were all the eighth students of SMP Makassar Raya in the 2023/2024 academic year, with the number of students was 27. Data collection techniques was carried out through observation of student activities, learning outcome tests and student responses to the application of the TPS of cooperative learning model. All data collected was analyzed by using quantitative and qualitative data analysis. Based on the results of observations of student activities with the application of the TPS of cooperative learning model, there was an increased from cycle I and cycle II with a percentage of 70.45% to 89.42%, and student responses to the application of the TPS of cooperative learning model that students were interested in the application of the TPS of cooperative learning model on the material of cubes and blocks with a percentage of 72.22% to 95.66%. Student learning outcomes increased classically from 74% in cycle I to 92.59% in cycle II. Based on the results of this study and data analysis it can be concluded that the application of the TPS of cooperative learning model can improve learning outcomes at the eighth-grade students of Makassar Raya.